PENGARUH PEMBERIAN PROBIOTIK TEMBAN, BIOVET DAN BIOLACTA TERHADAP PERSENTASE KARKAS, BOBOT LEMAK ABDOMEN DAN ORGAN DALAM AYAM BROILER - Akhadiarto, Sindu (Badan Pengkajian dan Penerapan Teknologi, 2010)
Probiotics is a feed additive in the form of life microorganisms that balance microorganism population in the digestive tract. This research was conducted to study the effect of addition of probiotics product into drinking water on percentage of carcass,body fat and edible offal. One hundred and fifty birds of day old chicks (DOC) of “Hybro-AM” strain were divided into 5 groups of treatments. The treatments were R0 (control diet+ drinking water without probiotics), R1 (R0 + Temban), R2 (R0 + Biolacta), R3 (R0 + Biovet), and R4 (commercial diet). Chicken were given diet and drinking water ad libitum. Percentage of carcass, boy fat and edible offal (heart, gizzard, lever, andcaecum) measured when 35 day old broiler chicken. Local feed (control died) and control with probiotics are feed with self formulation (R0, and R1 – R3). Control diet based on the needs of broiler chickens by the National Research Council(NRC).Results showed that treatments did not give significant effect (P>0,05) percentage of carcass, body fat and edible offal. Giving probiotics biovet produce better carcass percentage compared with controls and other treatments.